Persepsi Orang Tua Tentang Nilai-Nilai Pendidikan Islam Dalam Film Kartun Upin Dan Ipin Pada Episode Tema Ramadhan - Nilma Puspita; Intan Utami (JPT : Jurnal Pendidikan Tematik, 2024)
This research is motivated by the importance of the role of Islamic education. In the application of Islamic educational values ​​for children, it must be given according to their circumstances, one of which is by presenting educational entertainment that makes children happy and learns from the entertainment. Television shows such as films and educational videos can be presented to children as a fun learning medium. One of the films that has educational value about educational values ​​is the cartoon film Upin and Ipin, the episode of the Ramadan theme. This study was conducted to examine the parents' perception of the values ​​of Islamic education in the cartoon film Upin and Ipin, the episode of the Ramadan theme. The type of research used in this research is qualitative research, which is research that is intended to understand the phenomenon of what is experienced by the object of research by descriptive in the form of words and language. Based on the results of research that has been carried out by conducting interviews with 18 parent informants, the values ​​of Islamic education in the cartoon film Upin and Ipin in the Ramadan theme episode are religious values, moral messages, morals and tolerance as well as positive behavior. Such as teaching worship, teaching about prayer and fasting and being able to help children learn to pray and fast. In addition, moral messages such as helping, respecting elders, friendship, learning and playing together, protecting the environment, not lying. In the cartoon, Upin and Ipin tell of patience in fasting waiting to break the fast, patiently holding back hunger and thirst, being patient when there are trials in fasting. In the cartoon, Upin and Ipin provides lessons about morals, including morals towards God, morals towards oneself and morals towards fellow human beingsKeywords: Learning Media,Learning Videos, Concept Understanding